2022
DOI: 10.1039/d2ta00763k
|View full text |Cite
|
Sign up to set email alerts
|

Impact of processing conditions on the film formation of lead-free halide double perovskite Cs2AgBiBr6

Abstract: Lead-Free halide double perovskites with enhanced stability have gained attention as a promising environmentally friendly alternative to lead-based halide perovskites. Amongst different halide double perovskites, Cs2AgBiBr6 has shown attractive optoelectronic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…These findings are consistent with previous experimental studies. [ 33–37 ] However, simulations revealed that this trend does not necessarily hold if the carrier diffusion lengths (for electrons and holes) are much larger than what was assumed for the results shown in Figure 1 (100 and 300 nm for electrons and holes, respectively). The lowest diffusion length will always be the limiting factor for a low J sc .…”
Section: Standard Architecturementioning
confidence: 89%
See 1 more Smart Citation
“…These findings are consistent with previous experimental studies. [ 33–37 ] However, simulations revealed that this trend does not necessarily hold if the carrier diffusion lengths (for electrons and holes) are much larger than what was assumed for the results shown in Figure 1 (100 and 300 nm for electrons and holes, respectively). The lowest diffusion length will always be the limiting factor for a low J sc .…”
Section: Standard Architecturementioning
confidence: 89%
“…[ 23,24 ] Some suggest that the poor conductivity of Cs 2 AgBiBr 6 is due to a disordered arrangement of Ag/Bi octahedra in the perovskite lattice, [ 25 ] while others highlight the self‐trapping of charge carriers, [ 26 ] phase impurities, [ 27 ] changes in structural dimensionality (from 2D to 3D), [ 28 ] heavier carrier effective masses, [ 29 ] large exciton binding energies, [ 30 ] and carrier–phonon scattering. [ 31 ] From a device‐level perspective, several attempts have been made to improve the PV performance of Cs 2 AgBiBr 6 , including optimization of the band energy alignment with the transporting layer, [ 32 ] better selective contact, [ 33 ] heterojunctions with dye molecules, [ 34 ] utilizing mesoporous scaffolds, [ 35 ] minimizing pinholes on film surfaces, [ 36 ] increasing grain morphological sizes, [ 37 ] and defect passivation. [ 38 ] However, to date the maximum reported PV power conversion efficiency (PCE) of Cs 2 AgBiBr 6 remains at just above 3% with corresponding V oc and J sc values of 1.198 V and 4.5 mA cm −2 , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The spin-coating method 86 (see Fig. 3, scheme 3), solution deposition, 134 gas-phase anion exchange strategy, 135 etc. are popular methods used to prepare LFAIHDP thin films.…”
Section: Band Structuresmentioning
confidence: 99%
“…73 Abdelsamie et al systematically studied the solution deposition, synthesis, and extraction of Cs 2 AgBiBr 6 thin films. 134 Jiang et al successfully synthesized large-scale wide-bandgap Cs 2 AgBiCl 6 thin films via a gas-phase anion exchange strategy. 135 Gao et al employed the spin-coating method with and without an anti-solvent dropping protocol for the preparation of Cs 2 AgBiBr 6 thin films.…”
Section: Band Structuresmentioning
confidence: 99%
See 1 more Smart Citation